Kinetic Urbanism. An alternative imagination for the urban practice - Felipe Vera (Materia Arquitectura)
Currently the challenge for design in both, practice and research, is related in how to intervene an increasing “Kinetic Intensity” that has progressively acquired more agency that “Static Density” in the transformation of the urban space. Coming out of a tradition that has been developed with the focus in understanding legible and permanent urban morphologies, western urbanism has developed an imagination inspired in the hard city. This has left a gap in what refer to the understanding of open ended processes associated to softer urban tissues. This article discusses Rahul Mehrotra s notion of the Kinetic City, as an interpretation of Indian cities urbanism arguing that such concepts and ideas are that useful also for addressing problems in the realm of design and planning outside the Indian subcontinent.